DAMPAK PERUBAHAN VARIABEL EKONOMI MAKRO TERHADAP KINERJA KEUANGAN BUMN SEKTOR ENERGI - Kharisma, Dzulfikar; Sri Yani Kusumastuti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to analyze the impact of macroeconomic variables changes on the financial performance of energy SOE’s such as PT Pertamina (Persero), PT Perusahaan Gas Negara (Persero) Tbk, PT Perusahaan Listrik Negara (Persero). These impacts are projected by using Macro Stress Test model. The results showed that from five macroeconomic variables (GDP Growth, exchange rates, oil price, interest rates, and inflation), only two variables that significantly affected the financial performance of the energy SOE’s, there are exchange rate and oil prince that have positive impact on Pertamina and PGN while at the same time give the negative impact on PLN.